Achievement And Reward on Employees’ Discipline and Performance - Cendriyani, Yani (Acman: Accounting and Management Journal, 2023)
The present research examines the intermediary function of employee discipline concerning task performance. This study investigates the impact of achievement motivation and incentives on the work discipline of employees. The researcher employed a survey research methodology involving a sample of 100 employees working in the construction industry in Bandung. The study used the Partial Least Squares methodology for data analysis to establish the interrelationships among the variables under investigation. The analysis findings indicate a considerable influence of achievement motivation and incentives on work ethics, which consequently bears relevance for task execution. The findings suggest that organizations can enhance operational efficiency by cultivating a conducive work atmosphere and reinforcing employee competencies and drive.